Dynamics of Indonesian Islamic Law: Its Role and Impact on the Political and Legal System in Indonesia - Fuji Rahmadi P (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Indonesia, as the country with the largest Muslim majority in the world, has a rich and diverse Islamic legal tradition that continues to evolve over time. This research analyzes the dynamics of the role of Islamic law in Indonesia and its impact on the country's political and legal system. This research uses a normative legal approach by examining in depth the relevant legal content, identifying patterns of change, challenges and opportunities in the implementation of Islamic law in the political and legal context in Indonesia. The research results show that the role of Islamic law in the political and legal system in Indonesia is truly significant. Islamic law not only provides a moral and ethical basis for the formation of inclusive and just political policies, but also aligns the national legal system with Islamic values held by the majority of society. In addition, Islamic law provides specific guidelines in regulating various aspects of daily life, strengthens the legitimacy of the political system, empowers Muslim communities in the political process, and provides alternative dispute resolution based on the principles of Islamic law. The impact is enormous, not only reflecting the diversity and plurality of Indonesian society, but also strengthening the legal foundations that are inclusive, just and harmonious in creating harmony between citizens.